Texas, My Texas : Musings of the Rambling Boy - Taylor, Lonn, 1940-2019 (Book collections on Project MUSE., 2012)
In this collection of essays about Texas gathered from his West Texas newspaper column, Lonn Taylor traverses the very best of Texas geography, Texas history, and Texas personalities. In a state so famous for its pride, Taylor manages to write a very honest, witty, and wise book about Texas past and Texas present. Texas, My Texas: Musings of the Rambling Boy is a story of legacies, of men and women, times, and places that have made this state what it is today. People-real Texans-are the focus of the essays, making Texas, My Texas a rite of passage for anyone who claims Texan heritage.